Влияние детонационных наноалмазов на кинетику осаждения цинка из цинкатных электролитов - Буркат, Г.К.; Долматов, В.Ю.; Жарков, Д.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
In the present work an influence of detonation nanodiamonds (DND) on electrochemical process and quality of the obtained deposited zinc from alkaline zincate electrolyte was investigated. Optimum composition of zincate elctrolyte such as ZnO – 12 g/l, NaOH – 120,0 g/l, A1DM – 6 ml/l, DND – 5-10 g/l was determined. It was ascertained that the corrosion resistance (a major quality characteristic of zinc coatings) of the obtained coatings increases two-fold as the concentration of DND is increased from 1 to 10,0 g/l , also the current efficiency rises.